Entrepreneurial family firms - Hoy, Frank (Prentice Hall entrepreneurship series., 2010)
There is more to family business management than what is taught in the traditional business curriculum. This text provides an understanding of how to handle the intricate dynamics of the family and business systems, and how to successfully launch, join or lead entrepreneurial ventures in which family is involved.